Pharmacotherapy of Lower Respiratory Tract Infections in Elderly-Focused on Antibiotics - Yang Liu; Yang Liu; Yan Zhang; Yan Zhang; Wanyu Zhao; Wanyu Zhao; Xiaolei Liu; Xiaolei Liu; Fengjuan Hu; Fengjuan Hu; Birong Dong; Birong Dong (Frontiers Media S.A., 2019)
Lower respiratory tract infections (LRTIs) refer to the inflammation of the trachea, bronchi, bronchioles, and lung tissue. Old people have an increased risk of developing LRTIs compared to young adults. The prevalence of LRTIs in the elderly population is not only related to underlying diseases and aging itself, but also to a variety of clinical issues, such as history of hospitalization, previous antibacterial therapy, mechanical ventilation, antibiotic resistance. These factors mentioned above have led to an increase in the prevalence and mortality of LRTIs in the elderly, and new medical strategies targeting LRTIs in this population are urgently needed. After a systematic review of the current randomized controlled trials and related studies, we recommend novel pharmacotherapies that demonstrate advantages for the management of LRTIs in people over the age of 65. We also briefly reviewed current medications for respiratory communicable diseases in the elderly. Various sources of information were used to ensure all relevant studies were included. We searched Pubmed, MEDLINE (OvidSP), EMBASE (OvidSP), and ClinicalTrials.gov. Strengths and limitations of these drugs were evaluated based on whether they have novelty of mechanism, favorable pharmacokinetic/pharmacodynamic profiles, avoidance of interactions and intolerance, simplicity of dosing, and their ability to cope with challenges which was mainly evaluated by the primary and secondary endpoints. The purpose of this review is to recommend the most promising antibiotics for treatment of LRTIs in the elderly (both in hospital and in the outpatient setting) based on the existing results of clinical studies with the novel antibiotics, and to briefly review current medications for respiratory communicable diseases in the elderly, aiming to a better management of LRTIs in clinical practice.